Pre-hospital management of patients with chest pain and/or dyspnoea of cardiac origin. A position paper of the Acute Cardiovascular Care Association (ACCA) of the ESC. Issue 1 (March 2020) - Beygui, Farzin; Castren, Maaret; Brunetti, Natale Daniele; Rosell-Ortiz, Fernando; Christ, Michael; Zeymer, Uwe; Huber, Kurt; Folke, Fredrik; Svensson, Leif; Bueno, Hector; van't Hof, Arnoud; Nikolaou, Nikolaos; et al.
Chest pain and acute dyspnoea are frequent causes of emergency medical services activation. The pre-hospital management of these conditions is heterogeneous across different regions of the world and Europe, as a consequence of the variety of emergency medical services and absence of specific practical guidelines. This position paper focuses on the practical aspects of the pre-hospital treatment on board and transfer of patients taken in charge by emergency medical services for chest pain and dyspnoea of suspected cardiac aetiology after the initial assessment and diagnostic work-up. The objective of the paper is to provide guidance, based on evidence, where available, or on experts' opinions, for all emergency medical services' health providers involved in the pre-hospital management of acute cardiovascular care.